An international comparison of the contribution to job creation by high-growth firms - Österreichisches Institut für Wirtschaftsforschung, Vienna; Anyadike-Danes, Michael; Bjuggren, Carl-Magnus; Dumont, Michel; Gottschalk, Sandra; Hölzl, Werner; Johansson, Dan; Maliranta, Mika; Myrann, Anja; Nielsen, Kristian; Zheng, Guanyu (Vienna, 2018)
"This paper addresses three simple questions: how should the contribution of high-growth firms to job creation be measured? how much does this contribution vary across countries? to what extent does the cross-country variation depend on variation in the proportion of high-growth firms in the business population? The first is a methodological question which we answer using a more highly articulated version of the standard job creation and destruction accounts. The other two are empirical questions which we answer using a purpose-built data set assembled from national firm-level sources and covering nine countries, spanning the ten three year periods from 2000-2003 to 2009-2012. The basic principle governing the development of the accounting framework is the choice of appropriate comparators. Firstly, when measuring contributions to job creation, we should focus on just job creating firms, otherwise we are summing over contributions from firms with positive, zero, and negative job creation numbers. Secondly, because we know growth depends in part on size, the "natural" comparison for high-growth firms is with job creation by similar-sized firms which simply did not grow as fast as high-growth firms. However, we also show how the measurement framework can be further extended to include, for example, a consistent measure of the contribution of small job creating firms. On the empirical side, we find that the high-growth firm share of job creation by large job creating firms varies across countries by a factor of 2, from around one third to two thirds. A relatively small proportion of this cross-country variation is accounted for by variations in the influence of high-growth firms on job creation. On average high-growth firms generated between three or four times as many jobs as large non-high-growth job creating firms, but this ratio is relatively similar across countries. The bulk of the cross-country variation in high-growth firm contribution to job creation is accounted for by the relative abundance (or rarity) of high-growth firms. Moreover, we also show that the measurement of abundance depends upon the choice of measurement framework: the "winner" of a cross-national high-growth firm "beauty contest" on one measure will not necessarily be the winner on another."